2002
DOI: 10.1016/s0002-9440(10)64502-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved Contractile Function of the mdx Dystrophic Mouse Diaphragm Muscle after Insulin-Like Growth Factor-I Administration

Abstract: Limited knowledge exists regarding the efficacy of insulin-like growth factor I (IGF-I) administration as a therapeutic intervention for muscular dystrophies, although findings from other muscle pathology models suggest clinical potential. The diaphragm muscles of mdx mice (a model for Duchenne muscular dystrophy) were examined after 8 weeks of IGF-I administration (1 mg/kg s.c.) to test the hypothesis that IGF-I would improve the functional properties of dystrophic skeletal muscles. Force per cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 43 publications
(55 reference statements)
6
102
3
1
Order By: Relevance
“…9 Taking into account the pivotal role of calcineurin in maintaining the slow-twitch program and the phenotype-dependent expression of chloride channels, 19,46 it is feasible that the CsA treatment can increase gCl by reducing the proportion of fibers belonging to the slow phenotype, as supported by the observation that the low percentage of EDL fibers co-expressing the slow isoform of myosin heavy chain, was further reduced in CsA-treated mice. However, although this mechanism may account for the CsA effect on gCl of mdx DIA, in which a compensatory fast-to-slow phenotype shift has been described, albeit nonunanimously, 47,48 it cannot explain the drug effect in mdx EDL muscle because we confirmed that no functionally significant phenotype transition occurs in this fast muscle in response to either genotype or exercise. 29 We previously hypothesized, 9 that the decrease of gCl induced by exercise in EDL muscle fibers might be related to a short-term action of proinflammatory cytokines, produced in response to the damaging effect of exercise, on the function of chloride channel.…”
Section: Csa Exerts Different Effects On Functional Cellular Parametementioning
confidence: 51%
“…9 Taking into account the pivotal role of calcineurin in maintaining the slow-twitch program and the phenotype-dependent expression of chloride channels, 19,46 it is feasible that the CsA treatment can increase gCl by reducing the proportion of fibers belonging to the slow phenotype, as supported by the observation that the low percentage of EDL fibers co-expressing the slow isoform of myosin heavy chain, was further reduced in CsA-treated mice. However, although this mechanism may account for the CsA effect on gCl of mdx DIA, in which a compensatory fast-to-slow phenotype shift has been described, albeit nonunanimously, 47,48 it cannot explain the drug effect in mdx EDL muscle because we confirmed that no functionally significant phenotype transition occurs in this fast muscle in response to either genotype or exercise. 29 We previously hypothesized, 9 that the decrease of gCl induced by exercise in EDL muscle fibers might be related to a short-term action of proinflammatory cytokines, produced in response to the damaging effect of exercise, on the function of chloride channel.…”
Section: Csa Exerts Different Effects On Functional Cellular Parametementioning
confidence: 51%
“…We have demonstrated similar effects in previous studies, where recombinant IGF-I protein was delivered to mice at an identical dose via mini-osmotic pumps. 28,29 In these studies, systemic IGF-I protein administration induced morphological and functional changes, but IGF-I levels, as measured by RIA, were elevated in blood serum, but not in diaphragm or limb muscles. 28,29 Given its therapeutic potential to enhance restoration of muscle structure and function after damage, closer examination of the mechanisms of action of IGF-I at this dose and route of delivery is warranted.…”
Section: Discussionmentioning
confidence: 89%
“…28,29 In these studies, systemic IGF-I protein administration induced morphological and functional changes, but IGF-I levels, as measured by RIA, were elevated in blood serum, but not in diaphragm or limb muscles. 28,29 Given its therapeutic potential to enhance restoration of muscle structure and function after damage, closer examination of the mechanisms of action of IGF-I at this dose and route of delivery is warranted. It should be noted that the hastened functional recovery after electrotransfer could be directly related to higher IGF-I levels in regenerating muscle.…”
Section: Discussionmentioning
confidence: 89%
“…56,57 Postnatal treatment of mdx mice with subcutaneous IGF-1 demonstrated increased specific force and resistance to fatigue of diaphragm muscles. 58 Clinical trials of IGF-1 isoforms have not yet been attempted in DMD. However, recombinant human IGF-1 plus IGF-1 binding protein 3 is currently being studied in a phase II trial of myotonic muscular dystrophy (NCT00577577; clinical trials.gov).…”
Section: Modulation Of Muscle Growth and Regenerationmentioning
confidence: 99%